2010
DOI: 10.1186/1743-7075-7-89
|View full text |Cite
|
Sign up to set email alerts
|

Use of hamster as a model to study diet-induced atherosclerosis

Abstract: Golden-Syrian hamsters have been used as an animal model to assess diet-induced atherosclerosis since the early 1980s. Advantages appeared to include a low rate of endogenous cholesterol synthesis, receptor-mediated uptake of LDL cholesterol, cholesteryl ester transfer protein activity, hepatic apoB-100 and intestinal apoB-48 secretion, and uptake of the majority of LDL cholesterol via the LDL receptor pathway. Early work suggested hamsters fed high cholesterol and saturated fat diets responded similarly to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 124 publications
(381 reference statements)
3
68
0
7
Order By: Relevance
“…Recently, NHPs, pigs, dogs, and hamsters on atherogenic diets have been used as models of human atherosclerosis (60)(61)(62). The hamster model is questioned because no consistent lesion development has been observed in several hamster strains ( 63 ). Larger animals, such as dog, pig, and NHPs are more attractive due to the ability to apply interventional procedures and imaging on the larger vessels, making them more suitable as models for clinical practice ( 59 ).…”
Section: Suitable Preclinical Models For Dyslipidemia With Elevated Pmentioning
confidence: 99%
“…Recently, NHPs, pigs, dogs, and hamsters on atherogenic diets have been used as models of human atherosclerosis (60)(61)(62). The hamster model is questioned because no consistent lesion development has been observed in several hamster strains ( 63 ). Larger animals, such as dog, pig, and NHPs are more attractive due to the ability to apply interventional procedures and imaging on the larger vessels, making them more suitable as models for clinical practice ( 59 ).…”
Section: Suitable Preclinical Models For Dyslipidemia With Elevated Pmentioning
confidence: 99%
“…The morphology of aortic foam cells and lesions in hamsters fed atherogenic diets was reported to be similar to human lesions [70]. Recently, in a systematic review Dillard and colleagues concluded that the Golden-Syrian hamster does not appear to be a constructive model to determine the mechanism(s) of diet-induced development of atherosclerotic lesions (see review [71]) however the authors only concentrated on atherogenecity of cholesterol-and fat-rich diets in hamster models of atherosclerosis.…”
Section: The Hamster Modelsmentioning
confidence: 99%
“…They induced this model by feeding hamsters a highfat, high-cholesterol, inadequate methionine-and choline-containing diet. In addition to F1B hamster strain from Biobreeders (Watertown, MA) that commonly used to study dietinduced metabolic disorders other three outbred strains are Charles River (CR), Sasco and Harlan (see review [71]). All these strains are derived from inbred or outbred Golden-Syrian hamster.…”
Section: The Hamster Modelsmentioning
confidence: 99%
“…Even with the limited data to date, the inbred F1B hamster has been more consistently reported to develop an atherogenic lipoprotein profile than any of the other three outbred strains (i.e., CR, Sasco (Kahlon et al, 1996;Kahlon et al, 1997), and Harlan hamsters (Lock et al, 2005;Tyburczy et al, 2009); for a review, see (Dillard et al, 2010)). However, due to the inconsistent and unrepeatable results of aortic lesions in response to dietary fat type in recent studies, hamsters are no longer a suitable model for studying dietinduced atherosclerosis (Dillard et al, 2010) (Table 1).…”
Section: Hamstersmentioning
confidence: 99%
“…However, due to the inconsistent and unrepeatable results of aortic lesions in response to dietary fat type in recent studies, hamsters are no longer a suitable model for studying dietinduced atherosclerosis (Dillard et al, 2010) (Table 1).…”
Section: Hamstersmentioning
confidence: 99%